Survey on Pest and Disease of Corn (Zea Mays Linn) grown at BRIS Soil Area - Norhayati, Ngah; Abd Jamil, Zakaria; Salmah, Mohamed; Mohammad Hailmi, Sajili (2019)
A field survey was conducted to identified insect pest, beneficial insect and plant disease that associated with corn (Zea mays Linn) at BRIS soil area. Hybrid sweet corn variety Sugar King 516 was used as a sentinel plant in this study. All insect pest and beneficial insect observed at the experimental plot was collected and identified in the laboratory. Corn plant that shows the symptom of disease infection was collected for the isolation of pathogen and identification. The data on plant growth such as plant height, corn ear height, dry straw weight, ear weight, ear length, grain dry weight and shell weight was recorded. Data obtained shows the performance and adaptability of hybrid sweet corn variety Sweet King 516 in this experiment was comparable to the local hybrid sweet corn grown at other BRIS soil area at Terengganu. There is no strange pattern on the plant growth, thus prove that the insect infestation or disease infection does not disturb the plant development. Thirteen species of insect pest were identified. There are grasshopper (family Acrididae), katydid (family Tettigoniidae), sweet potato bug (Physomerus grossipes- family Coreidae), derbid plant hopper (Proutista moesta- family Derbidae), cotton stainer (Dysdercus sp- family Pyrrhocoridae), largid bug (Physopelta sp- family Largidae), corn leaf hopper (Peregrinus maidis- family Delphacidae), corn rootworms (Diabrotica virgifera- family Chrysomelidae), green chafer beetle (Anomala albopilosa- family Scarabaeidae) and tussock moth (Orgyia sp- family Erebidae). Three species of predatory insect were identified; Asian lady beetles (Harmonia axyridis- family Coccinellidae), transverse lady beetle (Coccinella transversalis- family Coccinellidae) and assassin bug (family Reduviidae). Two species of fungal pathogen that attacks corn in this experiment were identified as Fusarium sp. and Puccinia sp. Data obtained in this study provides info on pests and diseases associateed with corn, thus could be beneficial for the farmers to be prepared with the best pest and management strategies for their corn plantation at BRIS soil area.